Growth inhibition of Fusarium solani and F. oxysporum by Streptomyces sasae TG01, and its ability to solubilize insoluble phosphate - I Made Sudiana; ADELIA PUTRI; TOGA PANGIHOTAN NAPITUPULU; IDRIS; ISMU PURNANINGSIH; ATIT KANTI (Society for Indonesian Biodiversity, 2020)
Abstract. Sudiana A, Putri A, Napitupulu TP, Purnaningsih I, Idris, Kanti A. 2020. Growth inhibition of Fusarium solani and F. oxysporum by Streptomyces sasae TG01, and its ability to solubilize insoluble phosphate. Biodiversitas 21: 429-435. Actinomycetes have been widely explored for new antibiotic production, but not many studies explore its abilities to inhibit the growth of phytopathogenic fungi and solubilize insoluble phosphate hence stimulate the growth of plants. We isolated Actinomycetes from the soil. Based on morphology, physiology, and 16S rDNA analyses, the isolate is closely related to Streptomyces sasae. The strain was able to inhibit the growth of phytopathogenic fungi Fusarium solani, and Fusarium oxysporum. S. sasae produced secondary metabolites 2-methyl-1,3-dioxolane as the major constituent. The strain assimilated variable carbon sources include L-arabinose, D-fructose, D-glucose, D-mannitol, Lactose, raffinose, L-rhamnose, and sucrose. The strain grew at pH 6.0 to 8.0, and at salinity (1-3%). Their growth was affected by the salinity level. The strain solubilized Ca-P at 1-3% salinity, but their ability to solubilize phosphate was influenced by salinity. The strain was also able to solubilize rock phosphate. Their ability to solubilize less soluble phosphate and inhibit the growth of F. solani and F. oxysporum may imply that this strain is potential for biocontrol agents. The 16S rRNA gene was submitted to DDBJ with the entry number 5df623c1a3c8820021322a36.TG01, and the accession number is LC514451.